DOP36 Efficacy and safety of vedolizumab in patients with chronic active pouchitis refractory to anti-TNF therapy: Results of a retrospective multicenter study. (21st January 2022) - Sallette, M; Bouhnik, Y; Nachury, M; Bellanger, C; Laharie, D; Amiot, A; Peyrin-Biroulet, L; Roblin, X; Altwegg, R; Buisson, A; Reenaers, C; Bouguen, G; et al.
Abstract: Background: Total coloproctectomy with ileoanal anastomosis (IAA) is the procedure of choice for patients with treatment-resistant ulcerative colitis (UC). It is most often curative, but can be complicated by pouchitis in 30% of cases, which becomes chronic in 10% of patients. Its treatment is not codified after failure of conventional treatments and a first line of anti-TNF. The objective of our study was to determine the efficacy and safety of vedolizumab (VDZ) in patients with anti-TNF refractory chronic pouchitis. Methods: This was a retrospective, multicenter study conducted in 17 hospital centers. Patients were selected from July 2019 to January 2021. All patients had chronic pouchitis refractory to a first line of anti-TNF. We evaluated clinical, endoscopic and biological characteristics at initiation of VDZ therapy, at week (W) 10 as well as at W52. The primary objective of the study was to assess clinical response (improvement ≥ 50% in stool frequency and rectal bleeding) at W52. Secondary objectives were to assess clinical response and remission (absence of symptom) at W10, endoscopic response (improvement ≥ 50% of endoscopic lesions) and remission (mucosal healing) at W10 and 52. Adverse events were also collected. Results: Forty-nine patients were included in the study (23 women, 26 men, mean age 48 years). Thirty-one patients (63%) had received only one line of biologic. Forty-four (90%) patients had endoscopic evaluation before initiation of VDZ, and 25 (51%) patients at W10 and 52. CRP was assessed in all patients at baseline, 43 (88%) patients at W10, and 33 (67%) patients at W52.At W10, 17 (34%) patients were clinically responders without corticosteroids, of whom 3 (6%) were in remission; among the 25 patients evaluated, endoscopic response was obtanine in 5 (20%) patients and endoscopic remission in 11 (44%) patients. At W52, 22 (44%) patients were clinically responders, 12 (24%) of whom were in remission; endoscopic response was obtained in 15 (60%) patients and endoscopic remission in 5 (20%) patients. Although there was a trend for CRP to decrease during follow-up (17.3 mg/L at inclusion vs. 7.9 mg/L at W52) in the responder group, there was no significant difference between this subgroup and the non-responder patients at W52. Eight patients (16%) had adverse events, leading to discontinuation of treatment in three of them. Optimization of VDZ at W10 was the only factor predicting nonresponse at W52: 40% in the non-responder group vs 8% in the responder group (p=0.05). At 1 year, 69% of patients were continuing treatment. Conclusion: This retrospective multicenter study shows that VDZ is a therapeutic option that may be considered in the treatment of chronic pouchitis refractory to anti-TNF.